ChemInform Abstract: A General Method for N‐Glycosylation of Nucleobases Promoted by (p‐Tol)2SO/Tf2O with Thioglycoside as Donor. Issue 50 (December 2015) - Liu, Guang‐jian; Zhang, Xiao‐tai; Xing, Guo‐wen
Abstract: Based on a preactivation strategy using the (p‐Tol)2 SO/Tf2 O system, a series of nucleosides are synthesized by coupling various thioglycosides such as (I), (IV), and (VII) with pyrimidine and purine bases.